Genetic differentiation in life history traits and thermal stress performance across a heterogeneous dune landscape in Arabidopsis lyrata - Wos, Guillaume; Willi, Yvonne (Annals of botany, 2018)
Background and Aims: Over very short spatial scales, the habitat of a species can differ in multiple abiotic and biotic factors. These factors may impose natural selection on several traits and can cause genetic differentiation within a population. We studied multivariate genetic differentiation in a plant species of a sand dune landscape by linking environmental variation with differences in genotypic trait values and gene expression levels to find traits and candidate genes of microgeographical adaptation. Methods: Maternal seed families of Arabidopsis lyrata were collected in Saugatuck Dunes State Park, Michigan, USA, and environmental parameters were recorded at each collection site. Offspring plants were raised in climate chambers and exposed to one of three temperature treatments: regular occurrence of frost, heat, or constant control conditions. Several traits were assessed: plant growth, time to flowering, and frost and heat resistance. Key Results: The strongest trait-environment association was between a fast switch to sexual reproduction and weaker growth under frost, and growing in the open, away from trees. The second strongest association was between the trait combination of small plant size and early flowering under control conditions combined with large size under frost, and the combination of environmental conditions of growing close to trees, at low vegetation cover, on dune bottoms. Gene expression analysis by RNA-seq revealed candidate genes involved in multivariate trait differentiation. Conclusions: The results support the hypothesis that in natural populations, many environmental factors impose selection, and that they affect multiple traits, with the relative direction of trait change being complex. The results highlight that heterogeneity in the selection environment over small spatial scales is a main driver of the maintenance of adaptive genetic variation within populations.
Keywords: Environment; Life History Traits; rozmnožování; Genotype; Phenotype; vysoká teplota; Seeds; semena rostlinná; Reproduction; Hot Temperature; genetický drift; selekce (genetika); Flowers; genotyp; fyziologická adaptace; Selection, Genetic; Genetic Variation; Genetic Drift; podnebí; zvláštnosti životní historie; Adaptation, Physiological; ekosystém; životní prostředí; Ecosystem; Arabidopsis; fenotyp; Climate; genetická variace; květy